CULTURAL AND HISTORICAL PREREQUISITES FOR THE FORMATION AND DEVELOPMENT OF PRESCHOOL EDUCATION - Парфенова, Ольга Васильевна (Bulletin of the Chuvash State Pedagogical University named after I Y Yakovlev, 2020)
В статье представлены результаты изучения проблемы культурно-исторических предпосылок становления и развития дошкольного образования в России. Проанализировав имеющиеся историко-педагогические исследования в области дошкольного образования и установив их разнообразный и глубокий характер, автор доказал важность и актуальность выявления специфических предпосылок развития системы дошкольного образования. На основе анализа и систематизации данных историко-педагогических исследований, материалов архивов и периодической печати выявлена определенная связь между культурно-историческими предпосылками и этапами становления и развития дошкольного образования. С учетом культурно-исторических предпосылок в развитии дошкольного образования в России автором выделены два периода и этапы, отражающие специфику дошкольного образования в определенный исторический отрезок. Возникновение каждого этапа становления дошкольного образования в дореволюционный период (до 1917 года) обусловлено определенными предпосылками: патриархальным укладом жизни, общинным землепользованием, экономическими и социальными реформами Петра I и Екатерины II, обнищанием крестьян в период земельной реформы XIX века и их миграция в город, развитие производства, включение в производственный процесс женщин. Выделение этапов в развитии дошкольного образования в ХХ веке напрямую зависит от экономического развития. Изменения содержания дошкольного образования происходили под влиянием социокультурных факторов. Таким образом, культурно-исторические предпосылки определяют особенности дошкольного образования на разных этапах его развития. The article presents the results of studying the problem of cultural and historical prerequisites for the formation and development of preschool education in Russia. Analyzing the existing historical and pedagogical research works in the field of preschool education and revealing their diverse and deep nature, the author proved the importance and relevance of identification of specific prerequisites for the development of the preschool education system. Based on the analysis and systematization of historical and pedagogical research data, materials from archives and periodicals, the author revealed a certain relation between cultural and historical prerequisites and stages of formation and development of preschool education. Taking into account the cultural and historical background in the development of preschool education in Russia, the author identified two periods and the stages that reflect the specifics of preschool education in a certain historical period. The emergence of each stage of preschool education in the prerevolutionary period (before 1917) is due to certain prerequisites: Patriarchal lifestyle, communal land use, economic and social reforms of Peter I and Catherine II, the impoverishment of peasants during the land reform of the 19th century and their migration to the city, the development of production, the inclusion of women in the production process. The selection of stages in the evelopment of preschool education in the 20th century directly depends on economic development, changes in the content of preschool education occurred under the influence of socio-cultural factors. Thus, cultural and historical prerequisites determine the features of preschool education at different stages of its development.